2015
DOI: 10.1016/j.jjcc.2014.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Coronary vasodilation by the use of sublingual nitroglycerin using 64-slice dual-source coronary computed tomography angiography

Abstract: Sublingual nitroglycerin significantly enlarged the coronary diameters, especially in peripheral small coronary arteries, and increased the evaluable number of coronary segments on coronary CTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
(31 reference statements)
0
27
0
Order By: Relevance
“…Klass et al [ 22 ] showed that the relative vessel diameter increase is larger in distal segments compared to proximal segments. Okada et al [ 25 ] and Sato et al [ 23 ] confirmed this observation for peripheral segments. Kang et al [ 18 ] found a relative increase in diameter in two patients who underwent CCTA with and without administration of nitroglycerin.…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…Klass et al [ 22 ] showed that the relative vessel diameter increase is larger in distal segments compared to proximal segments. Okada et al [ 25 ] and Sato et al [ 23 ] confirmed this observation for peripheral segments. Kang et al [ 18 ] found a relative increase in diameter in two patients who underwent CCTA with and without administration of nitroglycerin.…”
Section: Resultsmentioning
confidence: 69%
“… 0.8 3 Sato, 2009 [ 23 ] 16-slice Randomized 60 100 70 0.3 ? Lee, 2011 [ 24 ] 64-slice Retrospective 67 100 61 0.6 5 Okada, 2014 [ 25 ] 64-slice DSCT Intra-individual 52 0 71 0.3 4 HR heart rate; bpm beats per minute; SNG sublingual nitroglycerin; + Korean language; # in tablet form; ° reported for overall study population, if only reported by group, then the group receiving nitroglycerin is reported; ^ β-blockers administered if HR > 65 bpm; ^^ β-blockers administered if HR > 70 bpm …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations